The ability of typically developing 2–3 year olds to infer the control mechanism for eye-gaze technology and the impact of causal language instruction. - Griffiths, Tom; Clarke, Michael T.; Swettenham, John (Disability & Rehabilitation: Assistive Technology, 2024)
Purpose: Little is known about how children learn to control eye-gaze technology, and clinicians lack information to guide decision-making. This paper examines whether typically developing 2–3 year olds can infer for themselves the causal mechanisms by which eye-gaze technology is controlled, whether a teaching intervention based on causal language improves performance and how their performance compares to the same task accessed via a touchscreen. Methods and materials: Typically developing children's (n = 9, Mean Age 28.7 months) performance on a cause and effect game presented on eye-gaze and touchscreen devices was compared. The game was presented first with no specific instruction on how to control the devices. This was followed by a subsequent presentation with explicit instruction about how the access methods worked, using a causal language approach. A final presentation examined whether children had retained any learning. Results: Performance in the eye-gaze condition without instruction (42.5% successful trials) was significantly below performance in the corresponding touchscreen condition (75%). However, when causal language instruction was added, performance with both access methods rose to comparable levels (90.7% eye-gaze and 94.6% touchscreen success). Performance gains were not retained post-intervention. Conclusions: Although 2–3 years in the study could make use of eye-gaze technology with support, this study found no evidence that these children could infer the causal mechanisms of control independently or intuitively. The lack of spatial contiguity and the comparative lack of feedback from eye-gaze devices are discussed as possible contributory factors. IMPLICATIONS FOR REHABILITATION: There are challenges in young children inferring for themselves the causal link between eye movements and control of an eye-gaze device. Explicit instruction may improve children's performance in a specific task, but it is debatable whether this translates to the establishment of causal mechanisms for control of the device. Clinicians should be cautious of making assumptions about what children are learning from activities claiming to teach cause and effect or other foundational eye-gaze control skills.